2023
DOI: 10.3390/electronics12071592
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Application Software Requirements Specification from Consumption Values

Abstract: In today’s society, mobile applications are becoming more popular and providing several advantages. However, users will resist using a product regardless of how well-tested or solid it is if the wrong requirements are implemented. Understanding the factors that influence the purchase of mobile applications can provide useful information for mobile application design and development. Hence, the purpose of this research is to better understand the impact of consumption values on customers in order to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The existing research concentrates on the responses to environmentally friendly products [ 24 ] or the consequences of various situational factors, making it difficult to determine how and why environmentally responsible consumer behavior varies among individuals [ 25 ]. Previous research on socially responsible consumption has explored individuals’ consumption behaviors [ 23 , 26 ]. Thus [ 24 ], suggested that changes in consumer behavior, such as substituting sustainably produced meat with green products, can reduce the environmental destruction and health issues caused by animal meat production and consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing research concentrates on the responses to environmentally friendly products [ 24 ] or the consequences of various situational factors, making it difficult to determine how and why environmentally responsible consumer behavior varies among individuals [ 25 ]. Previous research on socially responsible consumption has explored individuals’ consumption behaviors [ 23 , 26 ]. Thus [ 24 ], suggested that changes in consumer behavior, such as substituting sustainably produced meat with green products, can reduce the environmental destruction and health issues caused by animal meat production and consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consumers gain knowledge regarding the value of the consumed product, which is known as epistemic value. Finally, conditional value provides the perceived utility of the consumed product to change decision making [ 26 ]. Different factors affecting individuals' consumption values, such as health awareness, health motivation, and personal innovativeness, are new concepts in the consumption value theory.…”
Section: Literature Reviewmentioning
confidence: 99%